The Novel of War in Iran from the Perspective of the "Other" Presence Based on Bakhtin's Votes - Shokoofeh Arvin; Abolghasem Dadvar; Maryam Hosseini (Matn/Pizhūhī-i Adabī, 2019)
The "other" is one of the main concerns of Bakhtin and his works. In this research, with the aim of improving the quality of works and by analyzing Bakhtin's philosophical conception of otherness, we have been looking for the presence or absence of "another" in the novels of war and we studied these works in a descriptive-analytical Method. Findings show that the novels of war from this perspective can be divided into three categories: 1. works in which "the other" is briefly and indirectly mentioned. 2 works in which "the other" has many examples among characters, but eventually, he was influenced by the author's voice and condemned by his judgment. 3. works in which "other", in addition to a diverse presence in the form of characters, has equaled the position of the author and has led the work to multiplier and has moved the work to the polyphonic. In the present article, it has been analyzed in the following three works as examples of each category: Safar be Geray-e 270 Darageh (Journey to 270 degrees), Zemestan-e 62 (winter of 1362), Safar ba Mashin-e Ghiamat (Chess with Doomsday car).